2016
DOI: 10.1371/journal.pone.0161798
|View full text |Cite|
|
Sign up to set email alerts
|

Motor Experts Care about Consistency and Are Reluctant to Change Motor Outcome

Abstract: Thousands of hours of physical practice substantially change the way movements are performed. The mechanisms underlying altered behavior in highly-trained individuals are so far little understood. We studied experts (handballers) and untrained individuals (novices) in visuomotor adaptation of free throws, where subjects had to adapt their throwing direction to a visual displacement induced by prismatic glasses. Before visual displacement, experts expressed lower variability of motor errors than novices. Expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Darts experts showed a decreased variability compared to control groups which confirms that consistency (i.e. low variability) is a suitable marker of expertise 28,37 . Moreover, we found that transfer rates are correlated with variability and expertise.…”
Section: Discussionsupporting
confidence: 61%
“…Darts experts showed a decreased variability compared to control groups which confirms that consistency (i.e. low variability) is a suitable marker of expertise 28,37 . Moreover, we found that transfer rates are correlated with variability and expertise.…”
Section: Discussionsupporting
confidence: 61%
“…As a result, both novices and experts could adapt to the visuomotor rotation (Figure 3). Previous studies on motor learning in the upper limb movements have demonstrated that sensorimotor experience of task-related movements had an effect on motor learning of visuomotor rotation (Leukel et al, 2015;Kast and Leukel, 2016;Hewitson et al, 2020). It has been shown that experts rely on explicit strategies more than novices during adaptation (Leukel et al, 2015;Hewitson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that not all types of players, according to their experience level, might similarly benefit from augmented feedback. In previous studies it was demonstrated that augmented feedback was differently processed and deployed for learning by subjects with different experience levels in handball (Blazhenets, Kurz, Frings, Leukel, & Meyer, 2020; Kast & Leukel, 2016; Leukel, Gollhofer, & Taube, 2015). Thus, it might well be that different groups of subjects might utilize augmented feedback about the jumping height differently, resulting in different outcomes of jumping behaviour.…”
Section: Discussionmentioning
confidence: 99%